The siphonic energy transfer between hot solar wind and cold martian ionosphere through open magnetic flux rope - Xiaojun Xu; Lou-Chuang Lee; Qi Xu; Qing Chang; Jing Wang; Ming Wang; Shaosui Xu; Christian Möstl; Charles J. Farrugia; Xing Wang; Yudong Ye; Zilu Zhou; et al. (Fundamental Research, 2024)
A mechanism for energy transfer from the solar wind to the Martian ionosphere through open magnetic flux rope is proposed based on the observations by Mars Atmosphere and Volatile EvolutioN (MAVEN). The satellite was located in the dayside magnetosheath at an altitude of about 700 km above the northern hemisphere. Collisions between the hot solar wind protons and the cold heavy ions/neutrals in the subsolar region can cool the protons and heat the heavy ions. As a result, the magnetosheath protons are siphoned into the ionosphere due to the thermal pressure gradient of protons and the heated heavy ions escape along the open magnetic field lines. Although direct collisions in the lower-altitude region were not detected, this physical process is demonstrated by MAVEN measurements of enhanced proton density, decreased proton temperature and oppositely directed motions of hot and cool protons within the flux rope, which are very different from the observational features of the flux transfer events near the Earth’s magnetopause. This mechanism could universally exist in many contexts where a collisionless plasma region is connected to a collisional plasma region. By reconstructing the magnetic geometry and the cross-section of the flux rope using the Grad-Shafranov technique, the ion loss rates are quantitatively estimated to be on the order of 1023 s−1, which is much higher than previously estimated.